2018
DOI: 10.1055/a-0576-6667
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in scoring of Direct Observation of Procedural Skills (DOPS) forms and the impact on competence assessment

Abstract: Endoscopy assessors applied a greater range of scores using the new DOPS scale based on degree of supervision in two cohorts of trainees matched for experience. Our study provides construct validity evidence in support of the new scale format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 10 publications
1
61
0
Order By: Relevance
“…It follows the standard DOPS format of deconstructing a procedure into constituent steps (items), enveloped within broader groupings (domains). The gastroscopy DOPS was modified in July 2016 to include change to the 4-point scoring scale from a performance-based to a supervision-based (entrustment) scale [8], refinement of items and descriptors (following further working group review), and a generic domain for assessing endoscopic non-technical skills (ENTS). The updated gastroscopy DOPS contains 34 items, split into six domains, with each item accompanied by a detailed descriptor (Supplementary Fig.…”
mentioning
confidence: 99%
“…It follows the standard DOPS format of deconstructing a procedure into constituent steps (items), enveloped within broader groupings (domains). The gastroscopy DOPS was modified in July 2016 to include change to the 4-point scoring scale from a performance-based to a supervision-based (entrustment) scale [8], refinement of items and descriptors (following further working group review), and a generic domain for assessing endoscopic non-technical skills (ENTS). The updated gastroscopy DOPS contains 34 items, split into six domains, with each item accompanied by a detailed descriptor (Supplementary Fig.…”
mentioning
confidence: 99%
“…One area is the development of an assessment tool for NTS specific to the endoscopic setting. Although some existing tools incorporate NTS-related items, 41,42 there is no tool with strong validity evidence that is targeted solely towards endoscopic NTS. 43 Furthermore, a qualitative exploration of endoscopists', endoscopy nurses', and patients' perceptions of NTS would be valuable to inform future interventions.…”
Section: Discussionmentioning
confidence: 99%
“…6 In general, current evidence showed that workplace based assessment is not yet sufficient in terms of reliability but highly valid. [12][13][14][15][16] DOPS is not widely used in undergraduate dental education in Pakistan, but in light of findings of current study DOPs may enhance learning capacity of procedural skills in orthodontics at undergraduate level. However there are certain disadvantages of DOPS, such as, financial cost, time cost, and training of trainers and trainees and feasibility issues.…”
Section: Discussionmentioning
confidence: 99%